南極研究科学委員会の連続プランクトン採集器データベース グループワークショップ2018報告 - 高橋, 邦夫; タカハシ, クニオ; Kitchener, John A.; Robinson, Karen V.; Hosie, Graham W.; Takahashi, Kunio T. (国立極地研究所, 2019)
2018年11月20−23日にオーストラリア南極局にて「南極研究科学委員会，連続プランクトン採集器（以下CPR）データベース専門家グループワークショップ2018」を開催した．本ワークショップは2年に一度を目途に，南大洋CPR観測プロジェクト参加国の技術者を集め，各国間で統一された試料処理およびデータ管理を維持する目的で実施しており，今回は2016年に次ぐ開催であった．プロジェクトを主導する日本，オーストラリア，ニュージーランドの実務担当者の間で，動物プランクトンの種同定リストの更新，それに伴う具体的な分類カテゴリーの同定方法の確認を行った．特に亜南極域に出現するオキアミ類やカイアシ類について情報共有した．後半は観測データの品質管理，データ分析手法の再確認，また各国のマネージメントの状況を確認するとともに，今後の活動についての詳細な討議を行った．特に新規参入国へ向けた技術者育成ワークショップのための，分析手法マニュアル，および動物プランクトン種同定マニュアルの作成へ向けたロードマップを作製し，作業を開始することになった． The “Southern Ocean Continuous Plankton Recorder (SO-CPR) Survey Standards Workshop” was held at the Australian Antarctic Division on 20−23 November 2018. This biennial workshop was last held in 2016. The participants were technicians from the three nations (Japan, Australia, and New Zealand) leading the project. The purpose of the workshop was to ensure that high standards of data quality were being maintained, in terms of species identification and methodology, among the main analysts of the SO-CPR survey, and to discuss future training methods and a future roadmap for the SO-CPR program. A range of topics was discussed including: taxonomic resolution issues (particularly for northern species of copepods and euphausiids), laboratory methods (setting of the CPR cassette, microplastic counting rules), training methods (SO-CPR processing manual and zooplankton counting rule book), data handling for database input, and future standards workshops, including comprehensive training workshops for emerging SO-CPR survey partners. We discussed and agreed on a future roadmap for making a SO-CPR processing manual and zooplankton counting rule book, for the purposes of current and new technician training. departmental bulletin paper